2017
DOI: 10.18632/oncotarget.22185
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-derived AGEs enhance human gastric cancer metastasis through RAGE/ERK/Sp1/MMP2 cascade

Abstract: Advanced glycation end products (AGEs) have been reported to take part in many cancer processes. Whether AGEs contribute to gastric cancer (GC) course and the underlying mechanism are still unclear. Here, glucose-derived AGEs are detected to be accumulated in tumor tissues and blood of patients with GC. As the receptor for AGEs, RAGE is highly expressed in cancer tissues, and closely associated with the depth of cancer invasion, lymph node metastasis and TNM stage. Both in vivo and in vitro treatment of AGEs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…The RAGE-ligand signaling axis may promote the migration, invasion, and metastasis of a variety of cancers 5,14,44 . For example, the binding of RAGE and S100A8/A9 promotes the migration and invasion of human breast cancer cells 8 , and glucose-derived AGEs promotes the invasion and metastasis of gastric cancer through the activation of RAGE/ERK/Sp1/MMP2 pathway 45 . Moreover, expression of RAGE itself is also closely associated with the invasiveness and metastatic activities of gastric cancer 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The RAGE-ligand signaling axis may promote the migration, invasion, and metastasis of a variety of cancers 5,14,44 . For example, the binding of RAGE and S100A8/A9 promotes the migration and invasion of human breast cancer cells 8 , and glucose-derived AGEs promotes the invasion and metastasis of gastric cancer through the activation of RAGE/ERK/Sp1/MMP2 pathway 45 . Moreover, expression of RAGE itself is also closely associated with the invasiveness and metastatic activities of gastric cancer 6 .…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] It can bind to specific sites on the promoter of vascular endothelial growth factor (VEGF) or VEGF receptor, which further promotes the progress of tumors. 29 SP1-regulated tumor-related genes are involved in a variety of cell functions, including cell cycle (Cyclin D1, TGF-α, E2F1), 30,31 apoptosis (Bax, Bcl2), 32,33 tumor metastasis (TGF-β, MMP2) 34 and angiogenesis (VEGF). 35 According to our results, Syncytin 1 may be one of the targets of SP1 in regulating the function of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs family is known to cause chronic kidney disease, and kidney fibrosis present a failed wound healing in progressive chronic kidney disease (Klein, 2004). MMP-2 and MMP-9 are known to encourage cancer cell growth, including the metastasis of cancer cells (Deng, 2017) and has been shown to be profibrotic by induction of renal tubular cell epithelial-mesenchymal transition (Zhu, 2012). In the clinical studies demonstrated that serum MMP-2 and MMP-9 were higher levels in patients with type II Diabetes Mellitus (Signorelli, 2005;Derosa, 2007;Kostov, 2020).…”
Section: Discussionmentioning
confidence: 99%